Implementation of e-Government in Administrative Services at the Bangunrejo District Office - Rahmadayanti, Nova Pratiwi; Hartati, Sri (JLASA (Journal of Law and State Administration), 2024)
The implementation of e-Government in Bangunrejo District represents an innovative effort to enhance the quality of public services through digital technology. This system has improved administrative efficiency, expanded service accessibility, and increased government transparency. The results show a significant rise in public satisfaction, as services become faster, more convenient, and more secure. Furthermore, e-Government strengthens data protection and minimizes administrative errors. Despite challenges such as limited internet infrastructure and low digital literacy among citizens, strategic initiatives such as training programs and infrastructure development have been key to its success. Overall, the implementation of e-Government in Bangunrejo District has proven effective in realizing modern, transparent, efficient, and inclusive public services, supporting better governance that is responsive to community needs